The analysis of mass movement mechanism using limit equilibrium method (Bishop Method) and the analysis of retaining structure: a case study for Van province - Gör, Mesut (Gumushane University, 2021)
Slopes can be defined in two different ways as natural slopes or constructed slopes. Just because the slopes are natural or constructed does not always mean that they can be stable. As a result of exceeding the shear strength of the ground, instability of a slope occurs. The force causing this instability is determined and compared in terms of the shear stresses occurring along the movement surface and the shear strength parameters of the soil. Today, in parallel with technological developments, software has been developed that carry out slope stability analysis using numerical analysis and limit equilibrium methods. In this study, slope stability analyzes have been performed using the Slide v.06 software based on limit equilibrium method. The reason of a mass movement in Van province was determined with the aid of back analysis. Additional analyzes were carried out and the stability of the slope was examined for both dynamic and static conditions. In the light of the results obtained from the stability analyses, a reinforced concrete retaining wall has been suggested for slope stability durability. Reinforced concrete retaining wall geometry was modelled in the software and analyzes were made by using its technical specifications as input parameters. As a result of these constituted models, the slope is stable under dynamic conditions with the aid of the proposed retaining wall. © 2021, Gumushane University. All rights reserved.
Limit denge analizi (Bishop Yöntemi) ile kütle hareketinin mekanizması ve önlem yapısının analizi: Van ili örneği
Keywords: Limit equilibrium; Retaining wall; Slide; Slope stability